2020
DOI: 10.2147/cwcmr.s256537
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effect of <em>Aloe vera</em> Gel, <em>Calendula officinalis</em> Ointment and Simple Prophylactic Sacral Dressings for Pressure Injury Development</p>

Abstract: Background and Purpose: Prophylactic dressings play a significant role in the prevention of pressure injury. However, no herbal products have been used in this regard, so far. Therefore, the present study was designed with the aim of comparing the effect of Aloe vera gel, Calendula officinalis ointment and simple sacral prophylactic dressings on pressure injury development in patients admitted to intensive care unit. Materials and Methods: The sample of this clinical trial study consisted of 90 critically ill … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 25 publications
0
14
1
Order By: Relevance
“…showed the effectiveness of aloe vera gel in reducing the incidence of PUs in the sacrum. [ 22 ] However, in the present study, aloe vera alone showed no effects on the prevention of PUs. In explaining this difference, it could be said that in the present study, unlike Hekmatpou et al .…”
Section: Discussioncontrasting
confidence: 75%
See 3 more Smart Citations
“…showed the effectiveness of aloe vera gel in reducing the incidence of PUs in the sacrum. [ 22 ] However, in the present study, aloe vera alone showed no effects on the prevention of PUs. In explaining this difference, it could be said that in the present study, unlike Hekmatpou et al .…”
Section: Discussioncontrasting
confidence: 75%
“…Some studies have shown that aloe vera gel is effective in preventing PUs. [ 2 22 25 ] Hekmatpou et al . examined the effect of aloe vera gel compare to gels containing starch and water on the prevention of PUs which showed the positive effect of aloe vera gel on the prevention of PUs stage one.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aloe Vera is an excellent blend of more than 200 constituents, including polysaccharides (an intricate sugar), chemicals (complex proteins), glycoproteins, amino acids, nutrients and minerals which assists with lessening irritation, speed the recuperating of wounds, enhance torment, improve vascular stream, and diminish scarring (Baghdadi et al, 2020). Aloe Vera Gel seems to apply its calming movement through Brady kinase action and thromboxane B2 and prostaglandin F2 restraint (Kusmardi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%